2011
DOI: 10.1038/aja.2011.67
|View full text |Cite
|
Sign up to set email alerts
|

Genetic causes of spermatogenic failure

Abstract: Approximately 10%-15% of couples are infertile, and a male factor is involved in almost half of these cases. This observation is due in part to defects in spermatogenesis, and the underlying causes, including genetic abnormalities, remain largely unknown. Until recently, the only genetic tests used in the diagnosis of male infertility were aimed at detecting the presence of microdeletions of the long arm of the Y chromosome and/or chromosomal abnormalities. Various other single-gene or polygenic defects have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
124
3
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(140 citation statements)
references
References 146 publications
5
124
3
7
Order By: Relevance
“…The results revealed an overall frequency of Yq microdeletions to be 5.8 % (215/3,647) in the infertile individuals. This frequency is lower than those reported in meta-analysis (7.4-8.2 %) performed on world literature [13,18]. These observations imply that although the Yq microdeletions contribute towards male infertility in the Indian population, the association appears somewhat less than that observed in the Western counterparts.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…The results revealed an overall frequency of Yq microdeletions to be 5.8 % (215/3,647) in the infertile individuals. This frequency is lower than those reported in meta-analysis (7.4-8.2 %) performed on world literature [13,18]. These observations imply that although the Yq microdeletions contribute towards male infertility in the Indian population, the association appears somewhat less than that observed in the Western counterparts.…”
Section: Discussioncontrasting
confidence: 66%
“…Analysis of large datasets internationally has demonstrated the prevalence of Yq microdeletions in the range of 7-10 % [18,29]. The diagnosis of Yq microdeletions is considered to be clinically relevant for appropriate counseling and management of male infertility and is highly recommended for cases undertaking ICSI as a fertility treatment option owing to 100 % transmission of the genetic defect to the male offspring from fathers carrying the microdeletions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microdeletions involving the Azoospermia Factor loci (AZF) on the long arm of the Y chromosome (Yq) are a genetic cause of male infertility and the deletions of the AZFa, AZFb or AZFc loci alone or in combination occur in 2-10 % of men with abnormal seminogram [2][3][4][5][6]. Since Yq microdeletions can be vertically transmitted to the male offspring born after assisted reproduction [7,8], screening for these microdeletions has become a part of the routine diagnostic workup for men with azoospermia or oligozoospermia [5].…”
Section: Introductionmentioning
confidence: 99%
“…Microdeletions on the long arm of the Y chromosome (Yq), encompassing critical genes involved in spermatogenesis, has been observed in 5-10 % of infertile men [1,14,26,35]. In addition, mutations/polymorphisms in several autosomal genes have been identified in a subset of individuals with male factor infertility [15,26]. Genome-wide association studies have identified multiple autosomal loci across the genome that may be implicated in male factor infertility [10,18,21].…”
Section: Introductionmentioning
confidence: 99%